Thomas Herbst, Gunter Lorenz, Brigitta Mittmann and Martin Schnell (Editors). Lexikografie, ihre Basis- und Nachbarwissenschaften. (Englische) Wörterbücher zwischen 'common sense' und angewandter Theorie. - Smit, Maria (Lexikos, 2006)
The main aim of this volume, a collection of contributions by different authors, is to illustrate that dictionary making draws on other disciplines, and that lexicographical practice, in its turn, can feed neighbouring disciplines. The authors assert that linguistics is the basic discipline underlying lexicography, but the practice of dictionary making can, vice versa, expose problems of language analysis and especially crucial features of language, which should be taken into consideration in language theory. Often, lexicographical practice is characterized by devising ad hoc solutions to such problems that might positively influence the stringent and consistent approach in theoretical studies. In this sense, the relation between lexicography and linguistics should be seen as a mutual one, with possibilities of cross-fertilization in both ways. The authors want to show which trends in theoretical linguistics could be, or have already been, reflected in the compilation of dictionaries. They also want to demonstrate that many branches of linguistics, from semantics, via phraseology to syntax, can be enriched by lexicographical description and problems of lexicographical description. According to the introduction of the volume, the subtitle, "between 'common sense' and applied theory", especially characterizes the nature of lexicography practised in a meaningful way on the one hand, and on the other aptly refers to lexicographers themselves in their daily task.